2011
DOI: 10.2337/dc11-1039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Leptin Levels With Progression of Diabetic Kidney Disease in Patients With Type 2 Diabetes

Abstract: OBJECTIVETo clarify the association of serum leptin levels with progression of diabetic kidney disease in patients with type 2 diabetes (T2D).RESEARCH DESIGN AND METHODSThis was an observational cohort study of 668 patients with T2D. Patients were classified into three groups by sex-specific tertile of leptin levels. Outcome measurements were the rate of change in estimated glomerular filtration rate (eGFR) and progression to a more advanced stage of albuminuria.RESULTSPatients with low or high leptin levels h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Other biomarkers that have been associated with eGFR loss include: urinary high molecular weight adiponectin [118], adiponectin [119], type IV collagen [120,121], and haptoglobin [122,123]; circulating arginine vasopressin, as measured as copeptin [124], adipocyte FABP [125], fibroblast growth factor 21 [126], kininogen and kininogen fragments [127], the angiogenic factor leucine-rich a-2 glycoprotein 1 [128], the anti-ageing hormone soluble Klotho (low levels) [129], and leptin (both high and low levels) [130]; and erythrocyte total polyunsaturated fatty acids (PUFAs), n-3 PUFAs, and n-3/n-6 PUFA ratio, but not n-6 PUFAs (low levels) [106], all in T2D patients (except urinary collagen IV, in both T1D and T2D individuals). In addition, CKD273, a multidimensional urinary proteome classifier consisting of 273 protein fragments, predicted deterioration of renal function in patients with [131] and without [132] albuminuria and also development of microalbuminuria in normoalbuminuric individuals [133].…”
Section: Biomarkers Of Egfr Decline Beyond Albuminuriamentioning
confidence: 99%
“…Other biomarkers that have been associated with eGFR loss include: urinary high molecular weight adiponectin [118], adiponectin [119], type IV collagen [120,121], and haptoglobin [122,123]; circulating arginine vasopressin, as measured as copeptin [124], adipocyte FABP [125], fibroblast growth factor 21 [126], kininogen and kininogen fragments [127], the angiogenic factor leucine-rich a-2 glycoprotein 1 [128], the anti-ageing hormone soluble Klotho (low levels) [129], and leptin (both high and low levels) [130]; and erythrocyte total polyunsaturated fatty acids (PUFAs), n-3 PUFAs, and n-3/n-6 PUFA ratio, but not n-6 PUFAs (low levels) [106], all in T2D patients (except urinary collagen IV, in both T1D and T2D individuals). In addition, CKD273, a multidimensional urinary proteome classifier consisting of 273 protein fragments, predicted deterioration of renal function in patients with [131] and without [132] albuminuria and also development of microalbuminuria in normoalbuminuric individuals [133].…”
Section: Biomarkers Of Egfr Decline Beyond Albuminuriamentioning
confidence: 99%
“… Anti‐inflammation, anti‐oxidation and anti‐apoptosis: (a) islet inflammation and oxidative stress; (b) chronic adipose inflammation; (c) inflammatory cytokines (TNF‐α, IL‐6, IL‐1β) and chemokines (d) histone deacetylases; (e) 12/15‐lipoxygenase enzymes; (f) CXCR1/2 pathway intervention (CXCR1/2 neutralizing antibodies, CXCR1/2 antagonist, pepducin as a peptide inhibitor, Fractalkine (CX3CL1) ) (g) free fatty acid receptor 2 (FFAR2) agonists Stimulating insulin secretion: (a) enhancing incretin system (selective GLP‐1R agonists and DPP4 inhibitors) (b) sulfonylurea receptor 1(SUR1) agonists Insulin signal pathway: (a) insulin receptors (InsR) and its substrates (IRS1/2) expression; (b) Akt and AS160 (TBC1D4)/TBC1D1 phosphorylation (c) MAPKs; (d) glucose transporter 4 (GLUT4) expression or translocation; (e) PTP1B inhibition PPARγ agonists AMPK activation Suppression of α‐glucosidases SGLT2 inhibitors Key metabolic enzymes of neoglucogenesis, glycolysis, glycogenesis: (a) hexokinase (b) phosphofructokinase (c) glucose‐6‐phosphatase (d) fructose‐1,6‐bisphosphatase (e) liver glucokinase (f) glucose‐6‐phosphate dehydrogenase (g) pyruvate kinase (h) acetyl‐CoA carboxylases (ACCs) Rebalancing relevant hormones: (a) leptin; (b) adiponectin; (c) glucocorticoids …”
Section: Main Cellular and Metabolic Targets Against Diabetesmentioning
confidence: 99%
“…The UK Prospective Diabetes Study reported the differences in the risk factors for the two renal outcomes 35 . We have shown that leptin levels had different effects on kidney function decline and the progression of albuminuria in patients with type 2 diabetes 15 . Second, the number of patients reaching the end-point was small, yielding less statistical power to observe the interaction between leptin levels and obesity.…”
Section: Discussionmentioning
confidence: 94%